Effect of the Water-Air Coupling on the Stability of Rainfall-Induced Landslides Using a Coupled Infiltration and Hydromechanical Model - Biao Li; Bin Tian; Fuguo Tong; Chang Liu; Xiaoliang Xu (Geofluids)
The water and air flow in soil pores in response to rainfall infiltration is an important factor affecting the stability of rainfall-induced landslides. The objective of this paper is to investigate the effect of water-air flow on the deformation and stability of rainfall-induced landslides based on a coupled infiltration and hydromechanical model. The model is formulated by the water and air flow equation, the mechanical equilibrium, and porosity equations. The rainfall infiltration is introduced as a flux boundary, which is determined according to the comparison of the infiltration capacity and rainfall intensity. The numerical model and solution approach are validated by simulating the Liakopoulos drainage test and a rainfall infiltration experiment with satisfactory results. Taking the Tanjiawan landslide as a case study, the water and air flow in response to rainfall infiltration and its effect on deformation and stability are examined. The results show that the pore air is gradually trapped and compressed due to rainwater infiltration. The entrapped air has a slowing effect on the rainfall infiltration and a pushing-out effect on the front sliding body, which is an important driving force for the evolution of the slope deformation and stability due to rainfall infiltration.